Beclin 1 deficiency causes hepatic cell apoptosis via endoplasmic reticulum stress in zebrafish larvae. Issue 7 (20th December 2019) - Dong, Guoping; Zhang, Zhe; Duan, Kun; Shi, Wenpeng; Huang, Rui; Wang, Bangjun; Luo, Lingfei; Zhang, Yaoguang; Ruan, Hua; Huang, Honghui
Abstract : Beclin 1/Atg6 is an essential autophagy gene, and deficiency of this gene in organisms leads to impaired autophagic flux, usually with cell apoptosis; however, the causative mechanism of cell apoptosis is not clear. Here, we knocked out the beclin 1 gene in zebrafish and found that autophagic flux is disrupted in mutants. Beclin 1‐deficient zebrafish live through embryogenesis but die at larval stage. We found accumulated protein aggregates and vigorous apoptosis in mutant larvae, predominantly in the liver. The hepatic cell apoptosis in mutants results from an endoplasmic reticulum (ER) stress response; however, it is not the leading cause of mutant larval lethality. Our work proposes that ER stress induces cell apoptosis in Beclin 1‐deficient organisms. Abstract :